1997
DOI: 10.1093/ije/26.suppl_1.s137
|View full text |Cite
|
Sign up to set email alerts
|

Validation of dietary assessment methods in the UK arm of EPIC using weighed records, and 24-hour urinary nitrogen and potassium and serum vitamin C and carotenoids as biomarkers

Abstract: UK EPIC uses three methods (the 7-day diary, an improved FFQ, and the 24-hour recall) to assess diet. 93% of first food diaries are returned completed by participants. Repeated diaries are the main dietary assessment method for nested case-control analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
452
4
6

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(490 citation statements)
references
References 26 publications
28
452
4
6
Order By: Relevance
“…However, urine N appears to be a useful validator even when separated in time from intake measurements. Bingham et al (1997) found a correlation of 0⋅50 between the last 8 d of weighed records (seasons 3 and 4) and the first single urine specimen collected 6 or 9 months earlier in season 1. Further, in the present study, the correlation of EE with EI from weighed records (not measured concurrently) was 0⋅48, but that for EE and EI by diet history (measured within 2 weeks) was only 0⋅11.…”
Section: Discussionmentioning
confidence: 89%
“…However, urine N appears to be a useful validator even when separated in time from intake measurements. Bingham et al (1997) found a correlation of 0⋅50 between the last 8 d of weighed records (seasons 3 and 4) and the first single urine specimen collected 6 or 9 months earlier in season 1. Further, in the present study, the correlation of EE with EI from weighed records (not measured concurrently) was 0⋅48, but that for EE and EI by diet history (measured within 2 weeks) was only 0⋅11.…”
Section: Discussionmentioning
confidence: 89%
“…Participants completed a 131‐item validated FFQ 25, 26. Intakes of amino acids were derived predominantly using UK food composition data but with additional data from the U.S. Department of Agriculture 27, 28.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were asked to record their average diet over the past year by means of a list of food items and frequency categories. Nutrient intakes were calculated by multiplying the frequency of food consumption by standard portion weights to obtain the amount of food consumed per day; these were then converted into nutrient intakes using food tables [21].…”
Section: Subjects and Measurementsmentioning
confidence: 99%